O21 Effect of anesthetic strategy on procedural and clinical outcomes in primary distal medium-vessel occlusion stroke: results from the TOPMOST Registry. (29th August 2022) - Meyer, L; Broocks, G; Fehler, J; Hanning, U
Abstract : Introduction: Numerous questions regarding procedural details of thrombectomy for distal medium-vessel occlusions (DMVO) remain unanswered, including the optimal anesthetic strategy. 1 Aim of study: This analysis was performed to assess the effect of anesthetic strategies on outcomes and safety in patients undergoing distal thrombectomy. Methods: All available data of patients treated for primary DMVO of the anterior or posterior cerebral artery (ACA/PCA) including the A2-A3-A4 and P2-P3 segment, respectively, were analyzed from an international, retrospective, multicenter registry. Procedural characteristics were compared by the initial anesthetic strategy defined as general anesthesia (GA), or local anesthesia (LA) with or without conscious sedation (CS). Functional outcome was measured with the mRS. Safety was assessed by the occurrence of mortality and sICH. Results: At total of 233 patients met the inclusion criteria and were treated endovascularly for primary isolated DMVO. Patients were treated in 51.1% with LA ± CS (119) and in 49.9% under GA (114). The median age was 75 (IQR, 64–82) and 50.6% (118) were female. Procedural outcome did not differ significantly between groups of GA (mTICI 2b3: 83.3% (95)) and CS/LA (mTICI 2b3: 86.6% (103); p= 0.491). Excellent functional outcome (mRS 0–1) was higher in the CS/LA group (40.2% (27) vs. 63.9% (53); p=0.02) but not significant in multivariable logistic regression analysis. SICH occurred in 2.1% (5). Conclusion: The choice of anesthetic strategies did not affect the procedural or clinical outcome nor the safety of patients undergoing distal thrombectomy for primary isolated DMVO of the ACA and PCA. References: Saver JL, Chapot R, Agid R, et al . Thrombectomy for Distal, Medium Vessel Occlusions. Stroke 2020;0 (0):Stroke AHA.120.028956. DOI: DOI:10.1161/Stroke AHA.120.028956 Do you have any conflict of interest to declare? : No